PENETAPAN KADAR FENOLIK EKSTRAK METANOL RUMPUT POLYGALA (POLYGALA PANICULATA L.) DENGAN METODE KLT-DENSITOMETRI - Aktsar Roskiana ahmad; Dwiyanti Puspitasari; Virsa Handayani (Pengurus Pusat Ikatan Apoteker Indonesia, 2020)
Polygala grass (Polygala paniculata L.) is a plant that grows a lot in the Enrekang area, South Sulawesi. Polygala grass (Polygala paniculata L.) belongs to the Polygalaceae family which is widely used by the community as a medicine to treat wound. This study aims to determine the phenolic content in the methanol extract of polygala grass (Polygala paniculata L.). Methanol extract of polygala grass (Polygala paniculata L.) was obtained by maceration method with methanol P as solvent. Chemical component analysis used thin layer chromatography (TLC) method which was marked by the appearance of stains. The determination of phenolic content of methanol extract of polygala grass (Polygala paniculata L.) using the TLC-Densitometry method. The results showed that the phytochemical test on the methanol extract of polygala grass (Polygala paniculata L.) was positive for 35.280 µg of phenolic compounds.